PENGARUH KUALITAS LAYANAN WEBSITE SICEPAT EKSPRES DENGAN METODE WEBQEM TERHADAP KEPUASAN PENGGUNA - Sulistiowati Sulistiowati; Safira Wulandari Devianarko; Tony Soebijono (Majalah Ekonomi, 2022)
SiCepat Ekspres is a freight forwarding and logistics service company. SiCepat Ekspres has an official website at www.sicepat.com. The problem is that the increase in the number of visitors to SiCepat Ekspres is much lower than that of competing companies. To maintain and increase website users or visitors, it is necessary to know the relationship between website service quality and user satisfaction. Therefore, a research was conducted on the effect of website service quality with the WebQEM method on user satisfaction. The quality of website services with the WebQEM method has four variables, namely usability, functionality, reliability, and efficiency. With the distribution of questionnaires as many as 131 user respondents or visitors to the SiCepat Ekspres website, after being processed and analyzed by the multiple linear regression analysis method, it was obtained that 1) the reliability variable affected the user satisfaction variable by 32%, meaning that every increase in the reliability variable would increase user satisfaction by 32%. , 2) the efficiency variable affects the user satisfaction variable by 26%, meaning that every increase in the efficiency variable will increase user satisfaction by 26%, 3) the usability variable and the functionality variable have no effect on user satisfaction.